2021
DOI: 10.3389/fonc.2021.639745
|View full text |Cite
|
Sign up to set email alerts
|

The Position of EGF Deprivation in the Management of Advanced Non-Small Cell Lung Cancer

Abstract: Advanced non-small cell lung cancer (NSCLC) has faced a therapeutic revolution with the advent of tyrosine kinase inhibitors (TKIs) and immune checkpoints inhibitors (ICIs) approved for first and subsequent therapies. CIMAvax-EGF is a chemical conjugate between human-recombinant EGF and P64, a recombinant protein from Neisseria meningitides, which induces neutralizing antibodies against EGF. In the last 15 years, it has been extensively evaluated in advanced NSCLC patients. CIMAvax-EGF is safe, even after exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…This result suggests that subjects with squamous histology had greater benefits after vaccination since it is well accepted that the prognosis of adenocarcinoma patients is much better ( 40 , 41 ). Previous randomized clinical trials have also found a bigger effect in patients with squamous carcinomas, presumably associated with the greater expression of unmutated EGFR in this tumor type ( 42 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This result suggests that subjects with squamous histology had greater benefits after vaccination since it is well accepted that the prognosis of adenocarcinoma patients is much better ( 40 , 41 ). Previous randomized clinical trials have also found a bigger effect in patients with squamous carcinomas, presumably associated with the greater expression of unmutated EGFR in this tumor type ( 42 ).…”
Section: Discussionmentioning
confidence: 84%
“…This is precisely what is expected. EGF concentration after front-line therapy in NSCLC has been proposed as a poor prognostic biomarker of the disease and also as a predictive biomarker of higher CIMAvax-EGF efficacy ( 18 , 42 ). It means that patients with low EGF have a better prognosis, while patients with high EGF would have a poorer prognosis but a larger survival gain with CIMAvax-EGF.…”
Section: Discussionmentioning
confidence: 99%
“…The negative control group with EGF was significantly lower than the positive experimental group added with EGF only. When different concentrations of EGF were added to lung adenocarcinoma A549 cells, the protein expression level of EGFR increased to different degrees [ 44 ]. Bombyx mori carboxypeptidase inhibitor can inhibit the rapid proliferation of gastric cancer cells induced by the addition of EGF, which indicates that the inhibitory activity of silkworm carboxypeptidase inhibitor is likely related to the downstream-related pathways initiated by EGF/EGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent trials have demonstrated efficacy in lengthening the median overall survival of NSCLC patients with stable disease 110 …”
Section: Discussionmentioning
confidence: 99%